1993
DOI: 10.5014/ajot.47.6.541
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Persons With Psychiatric and Other Disorders

Abstract: Policy shifts toward fostering community inclusion of persons with disabilities have brought community attitudes (including attitudes of professionals) into sharper focus as a cause for concern. Using a social distance scale, this study examined the attitudes of cohorts of occupational therapy and business students toward persons with psychiatric and other disorders. Contrary to expectations, occupational therapy seniors did not demonstrate significantly different attitudes from occupational therapy freshmen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 17 publications
4
40
0
1
Order By: Relevance
“…During the past 20 years, numerous studies focused on the academic and social perspectives of students without disabilities toward individuals with disabilities, examining college major, year in college, gender, and level of contact with students with disabilities (e.g., Fichten, 1986;Lyons & Hayes, 1993;Upton et al, 2005;Yuker, 1994;among others). In a recent study conducted by Meyer et al (2012) on attitudes of students without disabilities toward students with learning disabilities and their accommodations, students from public and private institutions responded revealing few negative attitudes.…”
Section: College Students With Disabilities: What Are They Saying?mentioning
confidence: 99%
“…During the past 20 years, numerous studies focused on the academic and social perspectives of students without disabilities toward individuals with disabilities, examining college major, year in college, gender, and level of contact with students with disabilities (e.g., Fichten, 1986;Lyons & Hayes, 1993;Upton et al, 2005;Yuker, 1994;among others). In a recent study conducted by Meyer et al (2012) on attitudes of students without disabilities toward students with learning disabilities and their accommodations, students from public and private institutions responded revealing few negative attitudes.…”
Section: College Students With Disabilities: What Are They Saying?mentioning
confidence: 99%
“…The artful practitioner is one who can integrate all three forms of reflection. The use of an interactive journal that combines students' written reflections with written responses by faculty has been espoused as a tool that can foster reflection in practice (Crepeau, 1991;Lyons & Hayes, 1995;Peloquin & Davidson, 1993;Tryssenaar, 1995). Perhaps therapists can reflect on whether other views not identified in this study-perhaps correlating to the who (e.g., self-esteem, confidence), when (e.g., temporal adaptation) and where (choice of setting) of our situation-may further illuminate our art of practice.…”
Section: Reflection and The Three Viewsmentioning
confidence: 99%
“…There have been numerous articles and debates in the occupational therapy literature in North America in recent years on the decline of interest of occupational therapists and occupational therapy students in working in the field of mental health (Bonder, 1987;Scott, 1990;Lyons & Hayes, 1992;Pranger & Brown, 1992;Cusick, Demattia & Doyle, 1993;Falk-Kessler & Ruopp, 1993;Friedland & Renwick, 1993;Price, 1993). Picard-Greffe (1994, p. 248) reported that ' .…”
Section: The Context Of Professional and Practice Concernmentioning
confidence: 99%
“…By 1991 that figure had declined to 5% of published articles in our profession's journals. Authors have postulated that such factors as negative attitudes toward the severely mentally ill (Lyons & Hayes, 1992), the abandonment of occupational therapy's philosophy of holism (Friedland & Renwick, 1993), a lack of positive fieldwork experience (Cusick et al, 1993), the lack of prestige accorded to therapists working in mental health (Falk-Kessler & Ruopp, 1993), burnout (Pranger & Brown, 1992), and the 'negative image of the field' including 'images of low pay, limited success with chronic and revolving door patients, isolated working conditions, and blurred roles' (Price, 1993, p. 557) have influenced this diminished enthusiasm for mental health practice.…”
Section: The Context Of Professional and Practice Concernmentioning
confidence: 99%